UPLC/Q-TOF MS Screening and Identification of Antibacterial Compounds in Forsythia suspensa (Thunb.) Vahl Leaves - Zhou, Mingyue; Huo, Jinhai; Wang, Cairen; Wang, Weiming (Frontiers in Pharmacology, 2022)
Forsythia suspensa (Thunb.) Vahl (F. suspensa) is a traditional Chinese medical herb and only its fruit is currently used in clinical therapies. However, the discarded parts like leaves also contain a large number of active components. In this study, we used macroporous adsorption resin to enrich the effective components from F. suspensa leaves. The separated active compounds were then identified and quantified by ultra-performance liquid chromatography coupled with quadrupole time of flight mass spectrometry (UPLC/Q-TOF MS) and high-performance liquid chromatography Active components with antibacterial properties extracted from F. suspensa leaves were confirmed in vitro and the corresponding mechanisms were explored. In sum, a stable and effective method for extracting antibacterial active components from F. suspensa leaves was established in this study, which proved the practicability of F. suspensa leaves as traditional Chinese medicine and is conducive to the more comprehensive utilization of the plant.